A Study on Cybersickness Reduction Method using Oculomotor Exercise - Ho Kim, Yeol; Ko, Junho; Jang, Seong-wook; Seok, Kwang-Ho; Son, Wookho; Sang Kim, Yoon (International Journal of Engineering and Technology, 2018)
VR content has problem in causing cybersickness to user. Nevertheless, the main reasons causing cybersickness have not been identified. In this paper, we proposed a cybersickness reduction method using oculomotor exercise. The proposed method was examined through an experiment measuring human factors such as simulator sickness questionnaire (SSQ) and blood sampling. Experimental results with oculomotor exercise showed that cortisol in blood were not increased. Therefore, it was confirmed that the proposed method was effective for reducing cybersickness reduction.Â Â